Analysis of recipes of home-prepared diets for dogs and cats published in Portuguese - Pedrinelli, Vivian; Gomes, Márcia De O. S.; Carciofi, Aulus C. (Cambridge University Press (CUP), 2017)
The present study evaluated recipes of home-prepared diets for dogs and cats published in Portuguese. A total of 106 diets were evaluated: eighty for dogs, twenty-four for cats and two intended for both species. A commercial software package was used to analyse the diets, and an ingredient chemical composition database was built based on the Brazilian Tables of Food Composition and United States Department of Agriculture Nutrient Database. The estimated chemical composition of each recipe was compared with the Nutritional Guidelines for Complete and Complementary Pet Food for Cats and Dogs (Fédération Européenne de L'industrie des Aliments Pour Animaux Familiers; FEDIAF, 2014) recommendations for maintenance (as units/MJ). Most recipes (48 %) had no precise determination of ingredients and quantities. All diets had at least one nutrient below the recommendations, and all investigated nutrients were deficient in at least one diet. The most frequent nutrients below recommendation were: Fe (68·3 % of the recipes for dogs; 100 % of the recipes for cats); vitamin E (82·9 % of the dog recipes; 84·6 % of the cat recipes); Zn (75·6 % for dogs; 88·4 % for cats); Ca (73·2 % for dogs; 73 % for cats); Cu (85·4 % for dogs; 69·2 % for cats); choline (85·4 % for dogs; 69·2 % for cats); riboflavin (65·8 % for dogs; 11·5 % for cats); thiamine (39 % for dogs; 80·7 % for cats); and vitamin B12 (61 % for dogs; 34·6 % for cats). These recipes may potentially expose animals to nutritional deficiencies, and it is important to inform the owners of the risks of providing home-prepared diets. Better training of professionals that intend to prescribe home-prepared diets is advisable.
Keywords: Cat nutrition; Dog nutrition; Home-made diets; Nutritional deficiency